Primary Care Academy: lessons learned from a large-scale innovative primary care project - Steurs, Manon; Verté, Emily; De Loof, Hans; Weemaes, Isabel; Remmen, Roy; Anthierens, Sibyl; De Vriendt, Patricia (Frontiers in Public Health, 2024)
Introduction and contextThe social and healthcare system faces numerous challenges, with primary care playing a key role in achieving universal and equitable health coverage. However, the primary care field often struggles with limited research capacity, activity, and funding.The Primary Care AcademyTo address these gaps, the Primary Care Academy (PCA) - a large-scale, innovative, interdisciplinary research and networking organization, encompassing then organization in the primary care field, was established and funded in 2019 by the Fund Dr. Daniel De Coninck, a charity foundation, managed by the King Baudouin Foundation, attempted to fil this gap.ObjectivesThe aim of this study was identifying lessons learned on the implementation and achievements of a large-scale, innovative research and network organization, specifically the PCA.MethodThis study evaluates the PCA’s development process, focusing on its key achievements and critical elements by using a mixed-method data collection approach. After 5 years of rigorous collaboration, several lessons can be drawn regarding accomplishments and process flow, particularly in terms of a shared and clear vision, governance, leadership, and organizational culture.Discussion and conclusionThese lessons can inform future adaptations in the continuation of the PCA and serve as a guide for other caritative large-scale innovative initiatives.